A cross‐lagged model of depressive symptoms and mobility disability among middle‐aged and older Chinese adults with arthritis. Issue 10 (22nd August 2020) - Yang, Rumei; Wang, Jingxia; Wang, Haocen; Tracy, Eunjin Lee; Tracy, Cory T
Abstract : Aim: To examine the reciprocal and longitudinal associations between depressive symptoms and mobility disability in middle‐aged and older Chinese adults with arthritis. Methods: We used three waves of the China Health and Retirement Longitudinal Study. The analytic sample included 4682 community‐dwelling adults aged ≥45 years with arthritis who completed the self‐report measurement of depressive symptoms and mobility disability every 2 years over a 4‐year study period. Analysis involved an autoregressive cross‐lagged model. Results: The prevalence rates of comorbid depressive symptoms and mobility disability were 38.9%, 33.2% and 38.9%, respectively across three waves. There was a significant bidirectional and longitudinal relationship between depressive symptoms and mobility disability among middle‐aged and older Chinese adults with arthritis. A higher level of depressive symptoms in previous waves was associated with a subsequent increase in mobility disability over time. A similar pattern was also shown in the opposite direction from mobility disability to depressive symptoms over time. Conclusions: This study demonstrates that depressive symptoms and mobility disability are reciprocally related in Chinese adults with arthritis over time. In addition, it highlights the importance of early interventions aimed at reversing the downward spiral of depressive symptoms and mobility disability to improve the health of Chinese adults with arthritis. Geriatr Gerontol Int 2020; 20: 873–877 .